2013
DOI: 10.1016/j.bjid.2013.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of co-infections by HCV and HBV among Brazilian patients infected by HIV-1 and/or HTLV-1

Abstract: Infection by HCV and/or HBV is frequent among patients presenting retroviral infection, but risk factors and prevalence for each infection are distinct for each agent. Retroviral co-infection increases the risk of a positive AgHBs, but HTLV-1 infection seems to increase the likelihood of HCV spontaneous clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 20 publications
5
31
1
Order By: Relevance
“…In this study, the rate of active HBV infection in HIV patients was higher than in those with HCV (29.4% vs 0.7%). In comparison, this high rate of HIV/HBV co‐infection exceeds by far the global rate (10%) but is similar to studies performed in Brazil (27.5%) and Africa (28.4%) . In patients with HCV, the rate of HBsAg was 50% lower than reported in HCV patients in the U.S. (0.7% vs 1.4%) .…”
Section: Discussionsupporting
confidence: 87%
“…In this study, the rate of active HBV infection in HIV patients was higher than in those with HCV (29.4% vs 0.7%). In comparison, this high rate of HIV/HBV co‐infection exceeds by far the global rate (10%) but is similar to studies performed in Brazil (27.5%) and Africa (28.4%) . In patients with HCV, the rate of HBsAg was 50% lower than reported in HCV patients in the U.S. (0.7% vs 1.4%) .…”
Section: Discussionsupporting
confidence: 87%
“…The strong association between HTLV and HCV is due to the fact that these viruses share the same route of transmission. [22][23][24][25] Concerning the sensitivities of the assays for detecting HTLV-1 and HTLV-2 in HIV-infected individuals, we confirmed the results of previous studies conducted in our laboratory that have demonstrated difficulties in diagnosing HTLV-2 in HIV/AIDS patients. [11][12][13][14]20 The low sensitivity of the PCR assay in the present study was not due to low-quality DNA samples because the internal albumin control showed positive results.…”
Section: Discussionsupporting
confidence: 86%
“…For HIV-HCV co-infection, these frequencies have been reported as 10.7% [ 35 ] and 3.2% [ 36 ]. Salvador, another large city in Northeast—Brazil, has also been reported to have a large proportion of HIV-HBV co-infections (22%) and HIV-HCV co-infections (13%) [ 37 ]. Generally, lower frequencies for coinfections in our study may be explained by the fact that the above studies were performed with patients followed up in infectious disease-service centres at hospitals, whereas our study samples came from outpatients of VCTs who were newly diagnosed with HIV-1.…”
Section: Discussionmentioning
confidence: 99%